Exempla - Galbán, Juan Joseph
Fragmentary manuscript volume (154 leaves) containing exempla (comments) on the Ten Commandments (beginning with the third); the commandments of the church; dance, theater, and amusements (bayles, comedias, y galas); moral precepts; and punishments for disregarding the commandments and church feast days.
Roman Catholic priest in New Spain.
Collection material in Spanish.
Keywords: Catholic Church -- Mexico; Ten commandments; Amusements -- Religious aspects -- Catholic Church; Christian ethics -- Catholic authors; Dance -- Religious aspects -- Catholic Church; Exempla; Fasts and feasts -- Catholic Church; Punishment -- Religious aspects -- Catholic Church; Theater -- Religious aspects -- Catholic Church; New Spain; Clergy